The Effect of Compensation and Work Motivation on Teacher Job Satisfaction at Elementary Schools in Kahala Village, Kutai Kartanegara Regency - Muhammad Yassir Arafat; Catur Kumala Dewi; Sukirman Sukirman (STMIK Widya Cipta Dharma, 2026)
Teacher job satisfaction is an important factor that influences the quality of learning and the achievement of educational goals. Compensation and work motivation are factors that can affect teachers’ perceptions and attitudes toward their jobs. Appropriate compensation and high work motivation are expected to encourage teachers to perform their duties optimally and enhance their level of job satisfaction. This study aims to analyze the effect of compensation and work motivation on teacher job satisfaction at elementary schools in Kahala Village, Kutai Kartanegara Regency. This study employed a quantitative approach. Data were collected through questionnaires distributed to all 36 teachers using a saturated sampling technique. The data were analyzed using multiple linear regression with the assistance of Statistical Product and Service Solutions (SPSS). The results indicate that compensation does not have a significant effect on teacher job satisfaction. In contrast, work motivation has a positive and significant effect on teacher job satisfaction. Simultaneously, compensation and work motivation have a significant effect on teacher job satisfaction. The findings reveal that teacher job satisfaction is influenced not only by financial rewards but also by motivational factors that enhance enthusiasm, commitment, responsibility, and dedication in carrying out teaching duties. These findings highlight the important role of work motivation in creating a supportive work environment that contributes to improved teacher performance and job satisfaction. Therefore, schools and relevant stakeholders should strengthen teachers’ work motivation through recognition, supportive working conditions, and professional development opportunities to improve job satisfaction and enhance the quality of education.